Wage and work hour gap among radio broadcasters in Tacloban City. - Apas, Marvin V.; Ariza, Alexis Azzi B.; Perpiñan, Joamir A. (Marvin V. Apas, Alexis Azzi B. Ariza, and Joamir A. Perpiñan, 2019)
This paper aims to investigate the wage and work hour gap among radio broadcasters in Tacloban City. Specifically, this study wants to determine the factors contributing to the existing wage and work hour gap in the said field. The results of this study will provide a snapshot of the current status of radio broadcasting industry in the city in the background of the prevailing provision of employee rights and to present a glimpse of the industry for prospective radio broadcasters. The researchers identified three major classifications of radio broadcaster in terms of their employment status: regular, talent, and block timers. Block timers are excluded from the pool of respondents due to the reciprocal nature of employee-employer relationship and remuneration system, which the researchers deemed as unfit to the purpose of this study. A list of licensed radio broadcasters practicing within the region was obtained from the Kapisanan ng mga broadkasters ng Pilipinas. The list was supplemented and verified through a station to station survey throughout the city, with the roster of radio stations in operation provided by the National Telecommunications Commission. A total of 41 radio broadcasters were included as study participants. Percentage difference estimates showed determined an existing wage and work hour gap based on gender, employment status, and civil status. The Pearson r correlation analysis showed an inverse correlation between wage and hours worked as well as a similar relationship between work hours and employment status. Regression of dependent variable indicated that work hour, age, gender, civil status, and seniority are significant predictors of wages. Furthermore, wage, employment status, highest educational attainment, and seniority are significant predictors of work hour. Consistent with literature, it is observed that men are more likely to be assigned in higher positions as opposed to women. The researchers would like to recommend for further researches, investigation, and legislations that together, will improve the working condition, compensations, and benefits of radio broadcasters in the Philippines.